Biosorben Kulit Jengkol sebagai Penyerap Logam Pb pada Air Kolong Pasca Penambangan Timah - Fajar Indah Puspita Sari; Ristika Oktavia Asriza (LPPM Universitas Mataram, 2018)
Post-tin mining has caused a major problem in the Province of Bangka Belitung Islands, which leaves declining water quality of dam-water. The aim of this study is to employing jengkol shells to adsorb Pb metal from post tin-mining water. Biosorbent preparation from jengkol (Pithecellobium jiringa) shells was done by HNO3 activation. Metal absorption by biosorbent was applied to post tin-mining water. The functional groups involved in the adsorption process are studied by FTIR characterization. The results showed a shift of wave numbers in hydroxyl, sulfonyl and phosphate groups proving that these three functional groups were involved in absorb of Pb metal on the surface of biosorbent